Cryptanalysis and improvement of an efficient authenticated key exchange protocol with tight security reduction. (20th November 2014) - Lu, Siqi; Zhao, Jinhua; Cheng, Qingfeng
Summary: The SMEN protocol, proposed by Wu and Ustaoglu in 2009, has been considered to be secure as the authors claimed, and numerous theories are proposed based on this protocol. This paper analyzes the SMEN protocol and finds that this protocol is not resistant to the session corruption attack and the key compromise impersonation attack. Then, we propose an improved protocol with tight security reduction. Our improved protocol not only avoids the above attacks but also embraces the same efficiency as the SMEN protocol in terms of exponentiation. Besides, formal analysis of the improved protocol is presented by using the formal automatic security analysis tool Scyther. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper analyzes the SMEN protocol and finds that this protocol is not resistant to the session corruption attack and the key compromise impersonation attack. Then, we propose an improved protocol with tight security reduction. Our improved protocol not only avoids the above attacks but also embraces the same efficiency as the SMEN protocol in terms of exponentiation.